2005
DOI: 10.1681/asn.2004121089
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Bone Marrow-Derived Cells Contributes to Regeneration after Folic Acid-Induced Acute Tubular Injury

Abstract: Studies of tissue from recipients of bone marrow transplantation or organ allograft suggest that bone marrow-derived cells (BMDC) may differentiate into a variety of nonhematologic tissues, including renal tubular epithelium. The aims of this study were to examine whether BMDC contribute to recovery after acute renal injury and to assess the effects of cytokine mobilization on regeneration. Female mice (6 wk old) were lethally irradiated and transplanted with male bone marrow (BM) cells and later assigned into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
108
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 46 publications
10
108
1
1
Order By: Relevance
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Furthermore, ex vivo manipulation of macrophages using specific cytokines confirmed that classically activated, M1 macrophages worsen chronic inflammatory adriamycin nephropathy, whereas alternatively activated M2 macrophages reduce histological disruption and functional injury [36]. Of note, in the heart Camargo et al [37] have [39] Glycerol-induced ARF (mouse) MSCs Enhanced tubular proliferation [68] IR (rat) Papilla LRCs Proliferation and incorporation [149] IR (mouse) Bone marrow No functional improvement, intrarenal cells are the main source of repopulating cell during repair [22] Folic acid-induced acute tubular injury (mouse) Bone marrow Intrinsic tubular cell proliferation accounts for repair after damage [150] Folic acid-induced acute tubular injury (mouse) Bone marrow 10% incorporation in tubules and G-CSF doubles this rate [151] IR (rat) MSCs Improved renal function and less injury [152] Cisplatin-induced renal failure (mouse) MSCs Accelerated tubular proliferation [153] UUO (mouse) Bone marrow macrophages Reduced renal fibrosis [41] IR (rat) MSCs Improved renal function, increased proliferation and decreased apoptosis [84] IR (rat) rKS56 (S3 segment outgrowth) Replace tubular and improve function [80] Glycerol-induced tubulonecrosis (mouse) Human CD133 + cells Homing and tubular integration [66] UUO (rat) Label-retaining cells (LRC) Proliferates, migrates and transdifferentiates into fibroblast-like cells [27] Cisplatin-induced renal failure (mouse) G-CSF ± M-CSF Improvement in renal function and prevention of renal tubular injury [154] Anti-Thy1.1 GN (rat) MSCs Increased glomerular proliferation and reduction in proteinuria [53] Col4α3 deficiency (mouse) MSCs Prevented loss of peritubular capillaries and reduced fibrosis but no increase in function or survival [24] Col4α3 deficiency (mouse) Bone marrow Partial restoration of expression of the type IV collagen α3 chain, improved histology and function [25] Col4α3 deficiency (mouse) MSCs Improved function and glomerular scarring and interstitial fibrosis reduced [155] UUO (mouse) BM Instertitial BM-derived cells do not contribute significantly to collagen synthesis after damage [74] Adriamycin-nephropathy (mouse) Renal side population Functional amprovement but very low rate of engraftment. [78] IR (rat) Multipotent renal progenitor cells In vivo epithelial differentiation, no difference on renal function [67] Cultured met...…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Some experiments based on bone marrow transplantation indicated that bone marrow-derived stem cells may contribute to repopulate the injured nephrons. 10,11 MSCs were shown to localize within the injured kidneys when injected in mice with AKI. 3,5,6,12 However, several reports indicate only a transient recruitment of MSCs in the renal vasculature without a direct incorporation within the regenerating tubules.…”
mentioning
confidence: 99%
“…9,10 Others used drugs such as cisplatin or folic acid to induce AKI. 11,12 Here, we used a model of nephrotoxic AKI induced by HgCl 2 , based on a standardized survival evaluation protocol already published. 13 Mercuric chloride at high doses causes an increase in serum creatinine, urea, and potassium.…”
Section: Discussionmentioning
confidence: 99%